Interactive Media Development Based Macromedia Flash 8 on Themeliving Matter of Primary Class IV - Reffiane, Fine; Bayutama, Laksa (International Journal of Active Learning, 2019)
This study aims to determine the validity and practicality ofFlash-basedinteractive media Macromedia 8 on the theme of care for life mahkhluk Elementary School fourth grade. This research using research methodologies Research and Development (R & D). Steps to develop interactive media-based Macromedia Flash 8 using ADDIE model development procedure (Analysis, Design, Development, Implementation. andEvaluation).The validity of the media obtained from the results of expert validation consisted of three experts and three experts media material. The results obtained from the first media expert 97.5%, 97.5% II media experts and media experts III 100%. Results obtained from the subject matter experts I 98.33% 98.33% Second material experts and subject matter experts 96.66%. The average results obtained from the three media specialists and subject matter experts 98.33% 97.77% criteria "Very Decent Used". Practicality media obtained through the questionnaire responses of students and teachers Bendokatonkidul grade IV SDN, SDN 01 and SDN Tayu Purwokerto Wetan 01 on interactive media-based Macromedia Flash8.The results of the questionnaire responses fourth grade students of SDN Bendokatonkidul 98.59%, Purwokerto SDN 01 and SDN 100% 01 98.78% Tayu Wetan. The results of the questionnaire responses of teachers Kela IV SDN Bendokatonkidul 100%, Purwokerto SDN 01 and SDN 95% 01 92.5% Tayu Wetan. Average of questionnaire responses by 99.12% students and teachers' questionnaire responses by 95.83% with the criteria "Very Decent Used". The conclusion that interactive media-based Macromedia Flash 8 is valid and practical use on the theme of caring for sentient beings Elementary School fourth grade.